THE ROLE OF TELOMERIC PROTEINS AND THEIR RELEVANCE AS TARGETS IN ANTI-CANCER THERAPY - *, Wambua; *, BW; B.O, Olabu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The telomere is a region of vital nucleoprotein structures at the terminal end of the chromosome with 500- 3000 repeat sequences of TTAGGG. The shelterin and non-shelterin complexes are telomere associated proteins. These proteins protect chromosome ends from fusion and degradation. The non-shelterin complex of proteins is involved in DNA repair while the shelterin complex of proteins is responsible for regulating telomere length. Telomerase enzyme lengthens telomeres and in immortal cells it is activated. Approximately 90% of human cancers are telomerase positive. The inhibition of telomerase has been considered a safer approach than the use of cytotoxic drugs in anti-cancer therapy. However, the induction of delayed cell growth arrest via telomerase inhibition has been shown to be slow. This is due to the fact that the replication rounds required are too many for it to be effective. Induction of dissociation of shelterin proteins from telomeric DNA has been considered a more efficacious approach based on gene silencing and mutation studies. The loss of shelterin proteins such as the protection of telomeres 1 (POT 1) and telomere repeat binding factor 2 (TRF 2) in cancer cells has been associated with apoptosis of the tumour cells. Poly ADP ribose polymerase (PARP), a non-shelterin protein, is involved in DNA repair. Drugs such as PJ-34 and 3-Aminobenzamide have been developed as PARP inhibitors. Drugs that dissociate telomeric proteins from telomeric DNA are still under clinical trials, they include Quarfloxin, C-1305 and Telomestatin. These drugs have low cytotoxicity and are effective against tumours linked with dysfunction of DNA repair. The level of cytotoxicity of a drug is vital in determining its efficacy. The cytotoxicity of cellcycle inhibitors as anti-cancer medication motivated researchers to investigate telomeric proteins as targets of anti-cancer intervention. The dissociation of shelterin proteins from telomeric DNA and inhibition of non-shelterin proteins such as PARP and Tankyrase 1 and 2 have shown promising efficacy levels as anti-cancer therapy.